Circadian rhythms of blood pressure in hypertensive patients with cerebral microbleeds - Yang‐Kun Chen; Wen‐Cong Liang; Shu‐Lan Yuan; Zhuo‐Xin Ni; Wei Li; Yong‐Lin Liu; Jian‐Feng Qu (Brain and Behavior, 2022)
Abstract Background Whether the circadian rhythms of blood pressure (BP) contribute to the presence of cerebral microbleeds (CMBs) remains unknown. This study aimed to assess the relationship between nocturnal BP and CMBs in hypertensive patients. Methods This prospective case‐control study recruited 51 hypertensive patients with CMBs and 51 hypertensive patients without CMBs, matched with age and gender, serving as controls. A 24‐h ambulatory BP monitoring was conducted in all subjects. Differences in ambulatory BP parameters between the two groups were compared. Logistic regression analyzes were conducted to investigate the relationship between the ambulatory BP parameters and presence of CMBs. Results Patients with CMBs had a significant higher nocturnal mean SBP and lower relative nocturnal SBP dipping rate. Two logistic models were constructed to explore the association between ABPM indices and the presence of CMBs, adjusted with history of ischemic stroke and smoking. In model 1, higher nocturnal mean SBP positively correlated with presence of CMBs [standardized β = 0.254, odds ratio (OR) = 1.029, p = .041]. In model 2, the relative nocturnal SBP dipping rate was negatively correlated with CMBs (standardized β = −.363, OR = 0.918, p = .007). Only patients with deep CMBs had significant higher nocturnal mean SBP and lower relative nocturnal SBP dipping rate in comparison with those without CMBs. Conclusions Higher nocturnal SBP and lower relative nocturnal SBP dipping rate may be associated with CMBs in hypertensive patients.